Titanium Impurity Control in V-Bearing Pig Iron Prepared via the Sodium Smelting of Vanadium–Titanium Magnetite - Zhiwei Bian; Lei Cao; Desheng Chen; Hongxin Zhao; Tao Qi; Lina Wang; Yulan Zhen (Metals, 2023)
The sodium smelting of vanadium–titanium magnetite (VTM) can realize a multi-component comprehensive utilization of VTM. To broaden the application of the vanadium-bearing pig iron produced through this process, it is imperative to maintain the titanium content in molten iron at a very low level. In this study, the effects of temperature, the added amounts of sodium carbonate and anthracite, and the smelting time on the titanium content of molten iron were investigated using thermodynamic calculations and experiments. The results indicate that the introduction of sodium carbonate makes the reduction reaction of VTM a relatively low-temperature smelting system. In the smelting process, the Ti content in molten iron increases with the increase in temperature and decreases with the addition of sodium carbonate, while the amount of anthracite added has little effect on it. The appropriate technological parameters were determined as temperature: 1150–1250 °C, smelting time: ≥2 h, anthracite consumption: 25–35%, and sodium carbonate consumption: ≥60%. In addition, it was determined that the Ti impurities in the V-bearing pig iron were mainly (Ti,V)(C,N), CaTiO3, and Na2TiO3. All results obtained from this work contribute to the comprehensive utilization of VTM, and also provide theoretical support for the sodium smelting of VTM.